Theatre and performance design : a reader in scenography - Collins, Jane, 1951-; Nisbet, Andrew, 1960- (Routledge, 2010)
Theatre and performance studies, cultural theory, fine art, philosophy and the social sciences are here brought together in one volume to examine some of the principle forces that have informed the ways in which the visual practice of performance design has been produced and understood.